Les Actes de la Conférence de Carthage (411): un document trop ignoré du Bas-Empire - Lamirande, Emilien (Les Pères et la naissance de l'ecclésiologie, 2009)
Keywords: Donatisme

Quelques aspects de l’administration des provinces romaines d’Afrique avant la conquête vandale - Lepelley, Claude (Antiquité Tardive, 2003)
1. The Theodosian Code was compiled between 429 and 437. During these years the commissioners made much use of the archives in Africa, particularly those in Carthage when they were collecting those imperial constitutions which were retained in the new code. The fact that they were able to use these archives shows that in this region, which was not affected by the Vandals until 439, the records were well stocked and well maintained. 2. There is further evidence which shows that institutions were functioning normally: the Acts of the conference between the Catholics and Donatists at Carthage in 411, a passage from Salvian’s De Gubernatione Dei (probably informed about Africa by refugees he met in Marseilles), and testimony from Quodvultdeus, the exiled bishop of Carthage. 3. The Notitia Dignitatum, drawn up in 401, was partly revised for the West under Valentinian III. This document is not a theoretical organisational chart, and it provides evidence that in Africa a civil and military organisation was still complete and effective at the beginning of the 5th century. 4. It is recalled that there existed three distinct entities called Numidia: the province of this name (Numidia consularis); the western portion of Africa proconsularis, Numidia proconsularis‚ where the proconsul was represented by a legatus Numidiae; and lastly the ecclesiastical province of Numidia, which included both the civil province and the western part of Numidia proconsularis. 5. Two problems are examined: the complex question of the respective powers of the proconsul and the vicarius, and the problem of the location of the residence of the vicarius, who in 379 appears to have been forbidden to live in Africa proconsularis, even though certain offices of the vicariate still remained at Carthage. The vicarius appears to have returned subsequently to Carthage, but his tours of duty led him also to reside in other provincial metropoleis, particularly Cirta. 6. Regular functioning of the institutions is shown to have been disturbed by the corruption which was frequently denounced by the officials in charge. Certain of the letters of Augustine discovered by J. Divjak show that the phenomenon was aggravated on the eve of the Vandal conquest, probably linked to the disintegration of imperial authority which was a result of the invasions which were then rolling across Europe.
Keywords: Donatisme

This holy seed - Daniel, Robin (Tamarisk Publications, 2009)
Keywords: Donatisme

La persécution du donatisme et l'imposition de l'orthodoxie en Afrique du Nord (IVe-Ve siècles): comment effacer la mémoire des hérétiques ? - Buenacasa Pérez, Carles (Mémoire et histoire : les procédures de condamnation dans l'Antiquité romaine, 2007)
Keywords: Donatisme

From Donatist opposition to Byzantine loyalism: The Cult of Martyrs in North Africa 350-650 - Frend, William (Vandals, Romans and Berbers: new perspectives on late antique North Africa, 2004)
Keywords: Donatisme

Les circoncellions. Un mouvement ascétique itinérant dans l’Afrique du Nord des IVe et Ve siècles - Pottier, Bruno (Antiquités africaines, 2008)
This article re-examines the circumcelliones phenomenon, notably concerning their origins, their nature and the interpretations of their actions in Numidia during the 340’s. The agonistici, as they call themselves, seem to originate from donatist groups devoted to voluntary martyrdom from as early as 315. Circumcelliones were wandering ascetics from the first half of the fourth century, as it was shown in the book by a donatist bishop of Rome, Macrobius, devoted to the asceticism of confessores and virgins, and in the Contra Gaudentium of Augustine. The agonistici, as ascetics and martyrs, challenged the donatist bishops’ authority. Their actions can be interpreted as a kind of usurped ecclesiastical jurisdiction against those who they defined as pessimi homines. These people were publicly struck by rods which were called Israel. The circumcelliones formed a new Christian rural elite in Numidia, a region organized by imperial and private estates, which were infrequently promoted to city status.
Keywords: Donatisme

Who were the circumcellions - Shaw, Brent D. (Vandals, Romans and Berbers: new perspectives on late antique North Africa, 2004)
Keywords: Donatisme

Les circoncellions: Formation d'une élite rurale monastique autonome dans l'Afrique du Nord des IVe e Ve siècles - Pottier, Bruno (Revolte und Sozialstatuts von der Spaetantike bis zur fruehen Neuzeit, 2008)
Keywords: Donatisme

Circoncellioni - Frend, William (Nuovo Dizionario Patristico e di Antichità Cristiane, 2006)
Keywords: Donatisme

Furiosa turba: i fondamenti religiosi dell'eversione sociale, della dissidenza politica e della contestazione ecclesiale dei circoncellioni d'Africa - Cacitti, Remo (Studi di storia del cristianesimo e delle chiese cristiane, 2006)
Keywords: Donatisme

There is no crime for those who have Christ: religious violence in the Christian Roman Empire - Gaddis, Michael (The transformation of the classical heritage, 2005)
Keywords: Donatisme

L'apport d'actes des martyrs nouvellement découverts à la connaissance de la géographie historique de l'Afrique proconsulaire - Lepelley, Claude (Bulletin de la Société Nationale des Antiquaires de France, 2002)
Keywords: Donatisme

The Donatist Church: a movement of protest in Roman North Africa - Frend, William (Oxford scholarly classics, 2000)
Keywords: Donatisme

Les circoncellions : historiographie - Groslambert, Agnès (Les exclus dans l'antiquité: actes du colloque organisé à Lyon les 23 - 24 septembre 2004, 2007)
Keywords: Donatisme